A novel approach of using electrostatic field to improve economic losses during thawing and maintaining frozen beef quality - Corrette, Grace Elizabeth (Kansas State University, 2023)
Freezing is a long-practiced intervention to preserve meat quality during storage. However, the formation of ice crystals during freezing can cause physical damage to cell membrane resulting in negative impacts on quality characteristics. Therefore, the objective of this study was to evaluate the impact of applying an emerging technology of electrostatic field (EF) assisted thawing on the quality attributes of beef striploin. Beef striploins from both sides of 12 USDA Choice carcasses were halved, frozen at -40°C and thawed under 4 EF voltage treatments: 0 kV (control), 2.5 kV, 5 kV, and 10 kV. After reaching the internal temperature of - 1°C, striploins were weighed and swabbed for microbial content. Available purge was collected for protein concentration and microbial analysis, and then striploins were fabricated into steaks. The steaks were assigned to either 0- or 14- days aging and retail displayed for 0- or 7- days. During retail display, steaks were evaluated for discoloration and objective color measurements. Upon completion of retail display, steaks were utilized for Warner-Bratzler shear force (WBSF), cook loss, sarcomere length, troponin-T protein degradation, lipid oxidation, antioxidant capacity, pH, and proximate analysis. It was found that EF treatments increased purge loss compared to the control (P<0.05) and did not improve thawing speed (P>0.05), with 10kV EF taking longest to thaw (P<0.05). The 2.5 kV EF tended to decrease muscle fiber spacing compared to the control (P=0.09). There was no impact on aerobic plate counts for all EF voltages on the purge as well as the swabs on the surface (P>0.05). Samples aged for 0 days under 5kV EF showed more discoloration than those from the other treatments (P<0.05), and samples aged 14 days under 2.5kV and 5kV EF showed less discoloration than those from 0 kV and 10kV (P<0.05). Samples thawed under 10kV EF showed a reduction in WBSF compared to the control (P<0.05), but there was no impact of EF on microbial content, sarcomere length, troponin-T degradation, relative fat %, crude protein %, or moisture %, purge protein concentration, pH, lipid oxidation and antioxidant capacity for both the hydrophilic and lipophilic portion (P>0.05). Overall, our study found that there was no benefit to applying EF during thawing on yield and purge losses to provide an economic incentive. However, there are findings that indicate that the application of EF may improve tenderness and extend shelf-life of beef during retail display.
Keywords: Beef quality; Electrostatic field; Frozen; Thawing